2015
DOI: 10.1149/2.0291504jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chloride on PEFCs in Presence of Various Cations

Abstract: The performance and durability of Polymer electrolyte fuel cells (PEFCs) were investigated by separately introducing HCl and five different chloride salts (AlCl 3 , FeCl 3 , CrCl 3 , NiCl 2 , and MgCl 2 ) into the air stream of an operating fuel cell. Under the same operating conditions and at a fixed chloride (Cl − ) concentration of 50 ppm in air stream, it appeared that HCl affected the cell performance faster than the other chloride salts, therefore the presence of the cation in the contaminant solutions s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…But no Ca/Al is detected in the CCM. These results conform to our previous findings [7,8], which shows that highly hydrophobic nature of the microporous layer (MPL) in GDL acts as a barrier to the transport of contaminant solution into the CCM [11].…”
Section: Resultssupporting
confidence: 92%
“…But no Ca/Al is detected in the CCM. These results conform to our previous findings [7,8], which shows that highly hydrophobic nature of the microporous layer (MPL) in GDL acts as a barrier to the transport of contaminant solution into the CCM [11].…”
Section: Resultssupporting
confidence: 92%
“…[24][25][26][27][28][29][30] The CCMs were GORE PRIMEA Membrane Electrode Assemblies (GORE PRIMEA, W. L. Gore and Associates) with a Pt loading of 0.4 mg/cm 2 for both anode and cathode. Freudenberg C4 gas diffusion layers (Freudenberg FCCT SE & Co. KG, Germany) were used during assembly.…”
Section: Cell Testingmentioning
confidence: 99%
“…21 They suggested that these pinholes may have been promoted by the enhanced production of peroxide radicals catalyzed by Fe species through Fenton's reaction. They also reported that Al 3+ reduced ORR kinetics and changed the ORR mechanism from a predominantly 4-electron pathway toward a 2-electron pathway.Our group investigated the effect of different cations (Na [24][25][26][27][28][29][30] as well as modeled the effects of cation contamination on PEFC performance. 9,11 Cation selection was based on several levels of screening: present in the air and water filter samples collected worldwide, contaminants likely to be encountered based on the current and probable future usage, valence state, solubility, toxicity, availability, paucity of scientific or engineering data, and relevance in terms of materials of construction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we investigated effect of various metal cations (Na + , K + , Mg 2+ , Ca 2+ , Ni 2+ , Ba 2+ , Al 3+ , Cr 3+ , Fe 3+ ) with a combination of various anions ((Cl)ˉ, (OH) -, (ClO 4 ) -, (CO 3 ) 2-, (SO 4 ) 2-) by in-situ injection into the air stream of an operating fuel cell [21][22][23][24][25][26][27] as well as ex-situ contaminating the membrane electrode assembly (MEA) [19,28]. After the screening studies with various cations, one contaminant (Ca 2+ ) was selected for in-depth studies that was not well investigated and abundant in the nature.…”
Section: Introductionmentioning
confidence: 99%